Association of vertical rootpulling resistance with root lodging and grain yield in selected S1 maize lines derived from a tropical lowNitrogen population - Kamara, A.Y.; Kling, J.G.; Menkir, A.; Ibikunle, O. (Wiley, 2003)
Root lodging and poor soil fertility are major constraints to maize production in the Guinea savannah of West Africa. Vertical root-pulling resistance is an indicator of the rooting characteristics of maize cultivars and could be used to select cultivars which have higher resistance to root lodging, take up nitrogen efficiently and have high yield. Twenty maize breeding lines were evaluated in the southern Guinea savannah of Nigeria for vertical root-pulling resistance, yield and root lodging in the 2000 and 2001 cropping seasons. There were significant differences amongst the breeding lines for all the characteristics measured. Vertical root-pulling resistance correlated positively with grain yield (r = 0.71, P < 0.01). There was a moderate negative correlation between vertical root-pulling resistance and root lodging (r = −0.46, P < 0.05). This suggested that selecting for high root-pulling resistance will improve grain yield and reduce root lodging. There was no significant association between root lodging and grain yield (r = −0.14, P < 0.22). This was attributed to two factors; weak root systems and high cob weight, both of which caused significant lodging.